Prevalence of depression and anxiety among mothers of children with neuro-developmental disorders at a tertiary care centre, Puducherry - Nousheen Fatima; Palanivel Chinnakali; Sathish Rajaa; Vikas Menon; Nivedita Mondal; Venkatesh Chandrasekaran (Elsevier, 2021)
Background: Parents of children with neuro-developmental disorder (NDD) experience psychiatric disorders like depression and anxiety; and mother being the main care-giver is at a higher risk. Socio-demographic conditions of the families also augment depression. Objective: To estimate the prevalence of depression and/or anxiety among mothers of children with NDD availing care at a tertiary care centre, Puducherry, India. Materials and methods: We conducted a cross sectional study from among mothers of children with NDD attending the paediatric clinics between September and October 2019. All mothers were administered PHQ-9 and GAD-7 tools to screen for depression and anxiety, respectively. Those who failed the screens were administered the MINI International Neuropsychiatric Inventory (MINI-PLUS) version 7.0.2 to confirm the diagnosis of depression and anxiety. Prevalence of depression and/or anxiety were presented with 95% confidence intervals. Results: A total of 120 mothers were included. Of those, mothers of children with epilepsy were maximum (40%) followed by Attention Deficit Hyperactivity disorder (27%), Intellectual Disability (14%), Cerebral Palsy (12%) and Autism spectrum disorder (7%). Of the total, 52 mothers were screened positive for depression and46 (37.5%, 95%CI 29.2-46.4) were diagnosed with depression. As for anxiety, 91 mothers were screened positive and 52 (43.3%, 95% CI 34.7-52.3) were diagnosed with anxiety. 36 (30% 95% CI 22.3-38.6) mothers had both depression and anxiety. Conclusion: Depression and anxiety were common among mothers of children with NDD. Hence screening and counseling of these mothers need to be considered.